Diagnostic study on teachers’ beliefs and practices in foreign language assessment - Giraldo Aristizábal, Frank (Íkala, Revista de Lenguaje y Cultura, 2018)
This paper reports the findings of the qualitative diagnostic stage within an action research study whose purpose is to improve the language assessment literacy (LAL) of English teachers at a Colombian language institute. A questionnaire, interviews, and document analyses were used to inquire into beliefs and practices in the design of an achievement test. Findings suggest that these teachers believe tests should have core qualities that are partially mirrored in their practices. The research also highlights that beliefs and practices in test design exhibit a dynamic relationship. Conclusions are based on findings and provide information useful for professional development experiences in LAL.